Auditing Public Value Strategy: Lessons From Wales - Richard Baylis (Public Value Accounting: Current Issues and Future Trends)
While some public organizations with strategies to create public value (PV) are using approaches such integrated reporting to account for their socially-valuable innovation, most public audit regimes continue to focus on organizational outcomes such as efficiency and effectiveness. Because this situation necessitates a profound rethinking of the discourse and practices of public audit, this chapter presents a study of developments in Wales; the first country to revise its public audit system in response to legislation that requires public bodies to enact strategies that focus on creating a form public value (sustainable development). This chapter extends to the realm of public audit, an analytical framework of four types of work required to develop PV accounting systems (philosophical, political, managerial, and technical). Our findings show how leaders at the Welsh national audit body worked with stakeholders to conceive six principles of PV strategy audit that include consultation, reflexivity, and piloting. Their political work of audit development involved acting as ‘small-scale statemen’ to build a broad and stable agreement around their philosophy of PV audit. At the same time, the audit managers worked hard to maintain the independence of the public audit function by ensuring that activity was carried out under the governing code of practice. This finding signals an issue that will require careful management in other contexts where PV strategy audit is developed. Overall, this chapter extends audit scholarship to provide a step forward in reimagining and illustrating how public audit can be updated to account for PV strategy.